Bioinformatics identification of ferroptosis-related genes and therapeutic drugs in rheumatoid arthritis - Li, Xianbin; He, Andong; Liu, Yue; Huang, Yuye; Zhang, Xueli (Frontiers in Medicine, 2023)
Rheumatoid arthritis (RA) is a chronic immune disease characterized by synovial inflammation and bone destruction, with a largely unclear etiology. Evidence has indicated that ferroptosis may play an increasingly important role in the onset and development of RA. However, ferroptosis-related genes are still largely unexplored in RA. Therefore, this work focused on identifying and validating the potential ferroptosis-related genes involved in RA through bioinformatics analysis. We screened differentially expressed ferroptosis-related genes (DEFGs) between RA patients and healthy individuals based on GSE55235 dataset. Subsequently, correlation analysis, protein-protein interaction (PPI) network analysis, GO, and KEGG enrichment analyses were performed using these DEFGs. Finally, our results were validated by GSE12021 dataset. We discovered 34 potential DEFGs in RA based on bioinformatics analysis. According to functional enrichment analysis, these genes were mainly enriched in HIF-1 signaling pathway, FoxO signaling pathway, and Ferroptosis pathway. Four genes (GABARPL1, DUSP1, JUN, and MAPK8) were validated to be downregulated by GSE12021 dataset and were diagnostic biomarkers and therapeutic targets for RA via the regulation of ferroptosis. Our results help shed more light on the pathogenesis of RA. Ferroptosis-related genes in RA are valuable diagnostic biomarkers and they will be exploited clinically as therapeutic targets in the future.